MHD convective heat transfer in a discretely heated square cavity with conductive inner block using two-phase nanofluid model - Alsabery A. I.; Sheremet M. A. Mikhail Aleksandrovich; Chamkha A. J.; Hashim I. (2018, 2018)
Title screen